As mulheres ribeirinhas e os estudos acadêmicos sobre violência - NASCIMENTO, Gabriela da Silva (2024)
The research aimed to analyze how academic studies address the issue of domestic violence against women living on the banks of waterways, referred to here as "ribeirinha women." In this way, it critically discussed the evolution of public policies aimed at combating this violence, considering how it became a public issue, especially through the struggle of feminist organizations, and how the state has been implementing them. The historical milestone that delimits the research is the "Maria da Penha Law" (Law No. 11.340) of 2006. The methodology has a bibliographic research character, utilizing the Brazilian Digital Library of Theses and Dissertations portal. Consequently, to organize the research, a list of descriptors was created to categorize and obtain necessary data. From the data entered in the spreadsheet, the main criterion for filtering was whether the work applied to the social theoretical debate regarding women (as many works mention women—specifying ribeirinha women, even—yet under a biological perspective, primarily addressing issues related to health). As a result, it was noted that the majority of theses and dissertations mentioning ribeirinha women were written by other women; however, there is a significant lack of focus on gender issues in many of the texts. In general, these works do not discuss ribeirinha women and their intersections of gender identity, territory, race and/or ethnicity, sexuality, and class. Much of the research limits these women to their work and what they produce. When they do not do so, they reduce them to their reproductive roles, i.e., their status as mothers. Both limitations are facets of the capitalist system and, therefore, of colonialism, which the sociocultural population to which these women belong is still strongly affected by, according to Brazil's historical context. Thus, it was concluded that there is a lack of specific studies focused on these women (ribeirinhas) and their vulnerabilities to violence, confirming that academia persists in a colonial logic of epistemicide, rendering them invisible and contributing to a culture of systematic and colonial oppression.